1997
DOI: 10.1152/ajpcell.1997.273.4.c1378
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of epithelial tight junctions is associated with myosin light-chain phosphorylation

Abstract: Tight junctions serve as the rate-limiting barrier to passive movement of hydrophilic solutes across intestinal epithelia. After activation of Na+-glucose cotransport, the permeability of intestinal tight junctions is increased. Because previous analyses of this physiological tight junction regulation have been restricted to intact mucosae, dissection of the mechanisms underlying this process has been limited. To characterize this process, we have developed a reductionist model consisting of Caco-2 intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
425
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 493 publications
(445 citation statements)
references
References 34 publications
16
425
1
3
Order By: Relevance
“…The role of Na+glucose transport in the regulation of epithelial tight junction permeability was further confirmed using Caco-2 intestinal epithelial cells transfected with the intestinal Na+-glucose cotransporter, wherein the activation of the co-transporter increased and inactivation decreased the permeability of the epithelial cells (Turner et al, 1997). Further research showed that the phosphporylation of myosin light-chain (MLC) catalyzed by myosin light-chain kinase (MLCK) was necessary for Na+-glucose co-transport-induced tight junction permeability regulation since pharmacological inhibition of MLCK prevented both MLC phosphorylation and regulation of tight junction barrier function in cultured intestinal epithelial cells (Turner et al, 1997).…”
Section: The Leaky Epithelial Barrier In Intestinal Diseasesmentioning
confidence: 86%
“…The role of Na+glucose transport in the regulation of epithelial tight junction permeability was further confirmed using Caco-2 intestinal epithelial cells transfected with the intestinal Na+-glucose cotransporter, wherein the activation of the co-transporter increased and inactivation decreased the permeability of the epithelial cells (Turner et al, 1997). Further research showed that the phosphporylation of myosin light-chain (MLC) catalyzed by myosin light-chain kinase (MLCK) was necessary for Na+-glucose co-transport-induced tight junction permeability regulation since pharmacological inhibition of MLCK prevented both MLC phosphorylation and regulation of tight junction barrier function in cultured intestinal epithelial cells (Turner et al, 1997).…”
Section: The Leaky Epithelial Barrier In Intestinal Diseasesmentioning
confidence: 86%
“…We are far from understanding the regulation of each of these molecules and the interactions that very likely exist between them. It is becoming increasingly clear that tight junctions are altered by both physiological (Madara and Pappenheimer, 1987;Turner et al, 1997) and pathophysiological processes (Spitz et al, 1995;Yuhan et al, 1997;Philpott et al, 1998;Sonoda et al, 1999). Here, we examine the impact of an important and interesting enteric bacterial pathogen, enteropathogenic Escherichia coli, on the tight junction-associated, transmembrane protein occludin.…”
Section: Discussionmentioning
confidence: 98%
“…Contraction of this ring, which inserts into the cell membrane immediately beneath the tight junction, has been shown to be one mechanism by which paracellular permeability is increased. Both physiological (activation of Na 1 /glucose co-transporter; Madara and Pappenheimer, 1987;Turner et al, 1997) and pathophysiological (EPEC infection; Yuhan et al, 1997) stimuli have been demonstrated to activate this pathway. However, the effects of such stimuli on specific tight junction proteins have not been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In addition, phosphorylation of myosin light chain by myosin light chain kinase (MLCK) or by Rho kinases may also physiologically regulate paracellular permeability by placing tension on the tight junctional complexes. 10 An ever-increasing number of reports suggest that gastrointestinal pathogens may cause disease, at least in part, by increasing transepithelial permeability. For example, Helicobacter pylori has the ability to increase the passage of food antigens across the gastric epithelium, 11 and infection with this gastric pathogen may be associated with the development of food allergies.…”
mentioning
confidence: 99%